The Influence of Viral Market Marketing, Online Customer Review, Customer Trust on Purchase Decision of Scarlett Whitening Products in E-Commerce Shopee on Management Students of Muhammadiyah University of Gresik - Ahmad, Nur Khalidah; Surianto, Moh Agung (INNOVATION RESEARCH JOURNAL, 2025)
Rapid economic and technological developments in Indonesia have changed consumer behavior, especially in purchasing patterns that have shifted from physical stores to e-commerce. One industry that is experiencing significant growth is beauty care products, which are a primary need for many women. Competition in the cosmetics industry is increasing along with the development of beauty trends and product innovation. Data from the Ministry of Industry shows that the cosmetics industry increased by 9% in 2019. Many factors influence purchasing decisions, including viral marketing, buyer reviews and customer trust. Direct experience in trying the product. Even though online shopping is growing in popularity, many consumers still consider purchasing beauty products in person. One local brand that is experiencing rapid growth is Scarlett Whitening, which ranks second in sales of local skincare products with total sales of IDR 17.7 billion in the short period of 2022. This product has received BPOM permission and continues to grow as one of the most popular skincare brands in Indonesia. This research aims to determine the influence of Viral marketing, Online customer reviews, and Customer trust on Purchase decisions for Scarlett whitening products at E-Commerce Shope among Management students at Muhammadiyah University Gresik. The research method uses quantitative methods with a sample of 100 respondents. The data obtained was analyzed using multiple linear regression analysis techniques using the SPSS 20 program. The results of the research showed that Viral Marketing had a positive and significant influence on Purchase Decisions, Online Customer Reviews had a positive and significant influence on Purchase Decisions, while Customer Trust had a positive but not significant influence on Purchase Decisions.